2011
DOI: 10.15258/sst.2011.39.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different pretreatment methods on germination of Albizia julibrissin seeds

Abstract: The seeds of Albizia julibrissin are dormant because of their hard seed coat and they need pretreatment in order to germinate. In this research the effect of a) dry heating, at 30°C to 100°C for 10 to 60 min, b) chemical scarification with concentrated H 2 SO 4 for 15, 30, 60, 90 or 120 min, c) mechanical scarification for 5 sec, d) seed soaking in warm water (30°C to 100°C for one to six hours) and e) seed soaking in tap water for one to six days, on seed germination were examined. The most successful treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 7 publications
3
9
1
Order By: Relevance
“…Sanyang et al (2008) concluded that seeds of A. senegal treated with hot water for 10 min showed early germination. Seeds of Albizia julibrissin treated with hot water, soaking in warm water at 40°C and 50°C, and soaking period were 1-6 h. Seeds soaking in 40°C and 50°C showed 86-91% germination (Merou, 2011). Ixora seeds treated with hot water and showed 85% germination, this result close to Albizia results.…”
Section: Resultssupporting
confidence: 72%
“…Sanyang et al (2008) concluded that seeds of A. senegal treated with hot water for 10 min showed early germination. Seeds of Albizia julibrissin treated with hot water, soaking in warm water at 40°C and 50°C, and soaking period were 1-6 h. Seeds soaking in 40°C and 50°C showed 86-91% germination (Merou, 2011). Ixora seeds treated with hot water and showed 85% germination, this result close to Albizia results.…”
Section: Resultssupporting
confidence: 72%
“…Soaking seeds in cold water for 1 to 6 days had no significant effect on increasing the germination percentage, germination rate, and seed vigor index. Unlike our present results, Merou et al (2011) reported that seed immersion in tap water for 2 days resulted in 73% germi- Fig. 4.…”
Section: Effect Of Different Dormancy Breaking Treatments On Germinatcontrasting
confidence: 97%
“…The reason behind the low seed germination reported by them, compared to that of the present research, can be attributed to both the different experimental conditions (planting the treated seeds in trays containing sterile sand and keeping them in a growth room under a temperature range of 20-25 °C) and seed provenance. In this regard, Merou et al (2011) also found that the seed coat of Albizia julibrissin became permeable when seeds were immersed in sulfuric acid for 2 hours, which increased germination from 33% to 99%. Our results are consistent with those obtained in other studies of Fabaceae species in which acid scarification made the seed coat water-permeable, thus allowing seeds to imbibe and germination (Orozco-Almanza et al, 2003;Hu et al, 2009;Babashpour et al, 2011;Merou et al, 2011).…”
Section: Effect Of Different Dormancy Breaking Treatments On Germinatmentioning
confidence: 87%
See 1 more Smart Citation
“…This result demonstrated that above mentioned treatment had the destructive effect on embryo. It is notified that increasing in doses of sulfuric acid caused germination improvement and suggested chemical scarification in concentrated H 2 SO 4 for 2 hours [16]. In this research thiourea did not have a positive effect on germination improvement of C. persica.…”
Section: Discussionmentioning
confidence: 49%